Perlindungan Konsumen di Indonesia dalam Perspektif Kebijakan Publik (Analisis Kualitatif atas Fragmentasi Kelembagaan, Risiko Digital, dan Kesenjangan Pemulihan Hak Konsumen) - Muhammad Firzah (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Consumer protection in Indonesia faces a structural transition from conventional market disputes to complex public policy problems driven by digital markets, institutional fragmentation, and weak consumer redress. This article analyzes consumer protection in Indonesia from a public policy perspective using a qualitative descriptive method and policy analysis design. The study relies on documentary research using official regulations, government reports, complaint statistics, and peer-reviewed literature published mainly between 2018 and 2025. Data validity is strengthened through source triangulation by comparing official datasets from the Ministry of Trade/BPS, BPKN, OJK, YLKI, and international organizations. The findings show that consumer protection is challenged by four major issues: the expansion of digital and non-marketplace transactions, institutional fragmentation among regulatory bodies, the emergence of platform-based risks such as dark commercial patterns, and a persistent redress gap. Empirical data show that Indonesia's e-commerce transactions reached Rp1,288.93 trillion in 2024, while 84.21% of the transaction value came from non-marketplace channels. BPKN recorded 1,733 consumer complaints in 2024 with potential losses of Rp424.25 billion, yet recovered losses reached only about Rp44.82 billion. The article argues that consumer protection must shift from complaint-based and sectoral governance toward integrated, risk-based consumer protection. The study recommends Integrated Consumer Protection Governance through legal reform, platform accountability, national complaint data integration, online dispute resolution, collective redress, and digital compliance audit. Keywords: Consumer Protection; Public Policy; Digital Economy; Institutional Fragmentation; Policy Analysis; Indonesia;